Urban Air Mobility demand forecasting: modeling evidence from the case study of Milan (Italy) - Pierluigi Coppola; Francesco De Fabiis; Fulvio Silvestri (European Transport Research Review)
Abstract This paper presents the results of a demand forecasting study about the introduction of Urban Air Mobility (UAM) services in the metropolitan area of Milan (Italy). Demand forecasting is based on random utility mode choice models, which include factors related to the individuals’ perception of vertical take-off/landing and low altitude flying over urbanized areas. The use cases of UAM services include airport shuttles, intercity air connections, and “air-taxis”, i.e., UAM services for short-trips within the metropolitan area. Several scenarios have been considered based on the number of access points (“vertiports”) and UAM fare levels. The results indicate that airport shuttles have a modal share of trips to/from airports (for both business and leisure) in a range of 2-5%. They resulted to be more attractive than air-taxis, which have a modal share in a range of 1-3%. Furthermore, the probability of choosing UAM services for intercity travels decreases with the distance and the time required for access/egress to/from the vertiports, whose catchment areas are dependent on the level of service provided by competing modes (notably the presence of good railway and highway connections).